IMPLEMENTATION OF SPRINT LIFE CYCLE FROM AGILE METHODOLOGY WITH KNOWLEDGE MANAGEMENT CYCLE - Akbar Priyono Haryadi; Christina Juliane (Informatika, Universitas Jenderal Soedirman, 2022)
Companies in almost every industry are adopting Agile techniques to improve IT projects, manage marketing initiatives, and manage their businesses. With the sprint life cycle implemented in the company, knowledge management can always be updated. The research was conducted by collecting literature studies, conducting literature review analysis and proposing a theory of the results of the study analysis. Through this research, it is known that by implementing the sprint life cycle of Google Ventures in the Knowledge Management process that adopts the analysis of the framework initiated by Evans (2014), Wee and Chua (2013) , Akhavan (2009), Lettieri (2004), Chyi Lee (2000) can produce a basic theory regarding the application of the sprint life cycle in knowledge management, namely: (1) Identify, Create, and Understand, (2) Sketch and Innovation, (3) Decide and Organize, (4) Prototype and Codification , (5) Test, Use, Share, and Learn. With the ideas from the results of this study, it is possible to expand the previous KMC model by integrating the sprint framework pattern by linking several initiatives within the existing KMC. Produce KMC Sprints that have advantages based on the nature of the Agile methodology, namely speeding up change/knowledge creation time and adaptability.